Two new species of Fibuloides (Lepidoptera: Tortricidae) from eastern Thailand - Jaikla, Soraya; Pinkaew, Nantasak; Vitheepradit, Akekawat; Klangsap, Nathawat (Zootaxa, 2013)
Two new species of Fibuloides are described from eastern Thailand: F. tratensis Jaikla and Pinkaew, n.sp., and F. bulla Jaikla and Pinkaew, n.sp. Males of F. tratensis have modified labial palpi with specialized scales that have not been re-ported for other Tortricidae. Descriptions and illustrations of adults and genitalia are provided for the two new species collected from Trat Agroforestry Research and Training Station, eastern Thailand.